The Use of Code Switching in Efl Classroom - Kana, Irma Nirmala; Benu, Naniana Nimrod; Nenotek, Seprianus Arwadi; Beeh, Norci (Jurnal Basicedu, 2023)
This article discusses code-switching used by teachers during the teaching and learning of English as a foreign language in the classroom. This is the result of a case study at a junior high school in Lembata, East Nusa Tenggara which aims to reveal the types and reasons for code-switching used by teachers in teaching. Data was obtained by observation and interviews with three English teachers who teach in six classes. The research results show that teachers use three types of code-switching, namely inter-sentential, intra-sentential, tag code-switching, and inter-participant code-switching. The use of these types depends on the teaching and learning situation in the classroom. The use of code-switching is based on the reason that it is used as a translation, to increase vocabulary, explain difficult words or topics, change topics, clarify subjects, avoid boring situations, and provide information. The use of code-switching helps teachers to teach and students to learn English, especially for new learners